Prevention of thrombotic disorders by antithrombotic diet and exercise: evidence by using global thrombosis tests. (24th January 2018) - Yamamoto, Junichiro; Ijiri, Yoshinobu; Ikarugi, Hideo; Otsui, Kazunori; Inoue, Nobutaka; Sakariassen, Kjell S
Prevention of thrombotic disorders has priority over treatment. There are only two pathologically relevant tests which are suitable for measuring the overall thrombotic status both in experimental conditions and in humans. The Global Thrombosis Test (GTT) and the Global Parallel-Plate Thrombosis Test can detect the pathologically relevant global thrombotic status. These tests have been successfully used for monitoring the effect of antithrombotic drugs and for developing novel antithrombotic agents. By using GTT, varieties of fruits, vegetables, and regular physical exercise have been tested for the effect on global thrombotic status. This review discusses the published evidence for the benefit of diet of selected fruit and vegetable varieties and doing regular physical exercise on improving thrombotic status. Future clinical trials monitored by GTT or Global Parallel-Plate Thrombosis Test could decide on the effectiveness of an experimentally proven antithrombotic diet with regular physical exercise in the prevention of thrombotic diseases. Lay abstract: Prevention of deadly diseases like heart attack or stroke is more effective than treating patients with already progressed disease. Epidemiologic studies raised the possibility that eating healthy food and doing physical exercise may prevent thrombotic diseases. To create an 'antithrombotic diet', fruits and vegetables should be selected and the benefit of diet and exercise should be monitored in people. We found that the Global Thrombosis Tests are useful for both selection of antithrombotic diet components and monitoring thrombotic status of individuals.